Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 5 - Polynomials and Factoring - 5.2 Factoring Trinomials of the Type x2+bx+c - 5.2 Exercise Set: 49

Answer

$-a^4(a+15)(a-6)$

Work Step by Step

Factoring the negative $GCF= -a^4 $, the given expression, $ -a^6-9a^5+90a^4 ,$ is equivalent to \begin{array}{l} -a^4(a^2+9a-90) .\end{array} The 2 numbers whose product is $ac= 1(-90)=-90 $ and whose sum is $b= 9 $ are $\left\{ 15,-6 \right\}.$ Using these two numbers to decompose the middle term of the above trinomial, then \begin{array}{l} -a^4(a^2+15a-6a-90) \\\\= -a^4[(a^2+15a)-(6a+90)] \\\\= -a^4[a(a+15)-6(a+15)] \\\\= -a^4[(a+15)(a-6)] \\\\= -a^4(a+15)(a-6) .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.